2019
DOI: 10.31024/ajpp.2019.5.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of natural and modified seed gum

Abstract: Objective: The objective of the present work was to investigate the film coating potential of Fenugreek seed gum (FSG), Tamarind seed gum (TSG), using paracetamol as a model drug. Fenugreek seed gum Materials and Methods: (FSG), tamarind seed gum (TSG), paracetamol tablets, hydroxypropylmethylcellulose (HPMC) and sodium alginate (SA). Core tablets of paracetamol were obtained from a pharmacy shop in the local market and were evaluated for weight, diameters, thickness, hardness, friability, and disintegration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Moreover, Nayak et al also reported that hydrophilic FSM also binds with water to form viscous gel-structure, which barricades the pores on the surface of polymeric matrix [76] . Retardation of drug release from polymer matrix might be the synergistic effect of both viscosity and gel forming properties of FSM, which also corroborated with various earlier findings [48,[77][78][79] .…”
Section: Able 2: Percent Weight Loss Of 5-fu Sa Fsm Pm Dpm and Bfsupporting
confidence: 90%
“…Moreover, Nayak et al also reported that hydrophilic FSM also binds with water to form viscous gel-structure, which barricades the pores on the surface of polymeric matrix [76] . Retardation of drug release from polymer matrix might be the synergistic effect of both viscosity and gel forming properties of FSM, which also corroborated with various earlier findings [48,[77][78][79] .…”
Section: Able 2: Percent Weight Loss Of 5-fu Sa Fsm Pm Dpm and Bfsupporting
confidence: 90%
“…[ 7 , 8 ] HAGE-101912 showed proton pump inhibitory activity in both ex vivo and in vivo models, which may be because it contains a substantial concentration of polyphenols and flavonoids, which are known to exhibit significant proton pump inhibitory activity. [ 7 , 18 ]…”
Section: Discussion and C Onclusionmentioning
confidence: 99%
“…Gum Extraction from Samanea saman Seeds (11,12,13): Pods were dried in the oven at a temperature of 60°C for two days. Seeds were separated from pods and powdered separately.…”
Section: Methodsmentioning
confidence: 99%